THE STUDY OF STRONG ADHESION AND COMPRESSIVE STRENGTH FIBER CONCRETE USING WASTE CUTTING BANNER - Anisa Apriliawati; Anis Rahmawati; Ida Nugroho Saputro (Indonesian Journal Of Civil Engineering Education, 2016)
Abstract: The purposes of this reseach were to, (1) determine the admixture of  variations  in  the  presentation  increase  banner  waste  as  concrete  mix  to  the specific  gravity  weight  of  the  concrete;  (2)  the  admixture  of  variations  in  the presentation  increase  banner  waste  as  a  mixture  of  concrete  of  compressive strength in concrete; (3) the admixture of variations in the presentation increased banner  waste  as  concrete  mix  against  a  strong  adhesion on  concrete;  (4)Determine  the  influence  of  variations  in  presentation  of  additional  waste  as  a banner of compressive strength of concrete mix and optimum strong adhesion  on concrete. The method of this research was experimental method and data analysis techniques  used  regression  analysis.  Variables  in  the  study  are (1)  independent variables: increase banner variation of 0.00%; 0.20%; 0.40%; 0.60%; 0.80% and 1.00%,  (2) dependent variable: specific grafity, compressive strength and strong adhesion  of concrete the result increased variety of waste banner. The results of the study was, (1) The addition banner fiber has strong influence on the specific grafity of  concrete  (2)  There  was  strong  effect  on  the  compressive  strength  of concrete that cause of by banner fiber. The highest effect produced by the addition of fiber banner that was 0.20% which reach 21.79 MPa. (3) There was low effect on the strong adhesion of concrete that cause of banner fiber. The highest effect that produced by the addition of banner fiber that was 0.40%, which reach 51.09 kg/cm2. (4)  The effect of adding banners on compressive strength has a optimum percentage of 0.20% with compressive strength of 21.79 MPa. The effect of adding banner has a strong adhesion  with the optimum percentage of 0.40% the optimum value of 51.09 kg/cm2.